The Effect of Giving Watermelon Citrullus Lanatus and Cucumus Sativus Juice on Reducing High Blood Pressure in Elderly People with Hypertension - Vermona Marbun; Mitha Sinta Dewi; Riyen Sari Manullang; Renince Siregar; Emy Purwani; Riris Ocktryna Silitonga; Ani Anggriani; Andi Pranata (Adi Husada Nursing Journal, 2026)
Hypertension is a silent killer, because often people with hypertension do not feel any symptoms for years. Hypertension treatment consists of 2 therapies: pharmacological and non-pharmacological. In pharmacological therapy, hypertension can be treated with antihypertensive drugs, and in non-pharmacological therapy, a combination of watermelon and cucumber juice can be consumed. Watermelon contains the amino acid citrulline, which helps lower blood pressure, while cucumber contains minerals such as potassium, magnesium, and phosphorus. This study aims to determine the effect of a combination of watermelon juice (Citrullus Lanatus) and cucumber (Cucumis Sativus) on reducing blood pressure in elderly individuals with hypertension in RW 004, Sabajaya Village, in 2024. The research Design used is quantitative with a quasi-experimental approach. The sampling technique in this study was purposive sampling, with a sample size determined using the Frederer formula. Statistical tests used the Wilcoxon test. The sample in this study was 20 elderly respondents with hypertension. The results of the study showed a p-value of 0.001 < Î± (0.05), indicating that the combination of watermelon and cucumber juice reduced blood pressure in the elderly in RW 004 Sabajaya Village. This evidence supports the potential of non-drug approaches as valuable additions to hypertension treatment, encouraging clinicians and researchers to explore and adopt such alternatives.